TRADISI MELAWAT ANTAR DESA DALAM MENINGKATKAN UKHUWAH PADA MASYARAKAT (Studi Deskriptif Desa Padang Unoi Kecamatan Salang Kabupaten Simeulue) - Rusi Hamda Yuni; Ismiati Ismiati; Rofiqa Duri (Islamijah: Journal of Islamic Social Sciences, 2026)
This study discusses the tradition of melawat in Simeulue, particularly in Desa Padang Unoi, as a social practice that strengthens silaturahmi, ukhuwah, and collective identity. The research focuses on the process of implementation, its relevance in reinforcing ukhuwah, and the challenges arising from the tradition. The method used is qualitative descriptive research with participant observation and semi-structured interviews, supported by secondary data from literature. The findings show that melawat is carried out with clear organization, involving village and customary leaders, and remains relevant in strengthening Islamic brotherhood and social solidarity. The challenges include changes in youth interaction patterns, limited resources, and the demand to uphold Islamic norms. The conclusion emphasizes the importance of melawat as cultural heritage and a social instrument, with suggestions for greater youth involvement, stronger roles of religious and traditional leaders, and adequate resource support to ensure sustainability.Keywords: tradition melawat; community brotherhood; descriptive study; Padang Unoi village